Peran Adopsi Financial Technology (Fintech) dan Literasi Keuangan dalam Meningkatkan Keberlanjutan Lingkungan - Ramadhani, Rahma Hutami; Laksana, Rio Dhani (Faculty of Economics and Business, Jenderal Soedirman University, 2025)
Environmental sustainability is an effort to maintain the balance of ecosystems for the survival of future generations. Fintech, as a technological innovation in the financial sector, has the potential to accelerate the transition towards more environmentally friendly financial practices through efficiency and accessibility. Financial literacy, which encompasses individuals' understanding of financial products and services, can encourage wiser and more sustainable decision-making. The aim of this paper is to identify how the combination of fintech and financial literacy can contribute to environmental sustainability. The research method involves literature analysis and case studies to gain current perspectives on the impact of fintech and the level of financial literacy on sustainable practices. Findings indicate that the adoption of fintech, supported by adequate financial literacy, can enhance energy efficiency and reduce carbon footprints through better resource management. The value of this research lies in providing insights for policymakers and industry practitioners to encourage the integration of financial technology that contributes to environmental sustainability.